2015
DOI: 10.1097/dbp.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Medically Fragile Youth

Abstract: Bullying is a common child and adolescent phenomenon that has concurrent and long-term implications for victims' psychological, psychosomatic, social, and academic functioning. Youth with chronic illnesses are at increased risk for being bullied, but few studies have evaluated specific risk and protective factors for medically fragile youth. Despite recommendations by the American Academy of Pediatrics and the Society for Adolescent Medicine that pediatric health care providers should contribute to bullying pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 186 publications
(190 reference statements)
1
10
1
Order By: Relevance
“…Many studies have shown that youth with chronic illness or disability are more likely to be bullied [17, 18] which is in contrast to our data. We would speculate some uncollected information may explain these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies have shown that youth with chronic illness or disability are more likely to be bullied [17, 18] which is in contrast to our data. We would speculate some uncollected information may explain these findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Research provides evidence of the critical importance of managing the school climate and involving as much as possible all school personnel in the reduction and elimination of bullying [18,53,54,55,56,57]. Results of this study show a number of key findings.…”
Section: Discussionmentioning
confidence: 49%
“…Students with disabilities also suffer the same immediate and long-term negative physical and psychosocial problems associated with victimization as students without disabilities. Programs are being developed that address these issues as part of the school-wide climate change and antibullying agenda [53,54,55,56,57]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite the increased risk factors for bullying in this population, there are currently no known studies that have specifically examined bullying perpetration or victimization among individuals with 22q. As a relevant comparison, children with chronic illness, complex medical conditions (e.g., asthma, inflammatory bowel disease, diabetes), and motor skills/coordination difficulties all have been noted to be at increased risk for bullying victimization (Bejerot et al, 2013; Faith et al, 2015; Pittet et al, 2010). Given the host of medical, physical, and neurodevelopmental challenges that typically present in individuals with 22q, there is a real concern about their increased risk factors for bullying victimization.…”
Section: Q112 Deletion Syndromementioning
confidence: 99%